2019
DOI: 10.1186/s13018-019-1359-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of core decompression for the treatment of femoral head necrosis: a systematic review and meta-analysis

Abstract: Background Core decompression (CD) is an important method for the treatment of osteonecrosis of the femoral head (ONFH). Few articles investigate the influence of core decompression on outcomes of ONFH. This study was carried out to observe the safety and effectiveness of core decompression in the treatment of ONFH. Methods A comprehensive literature search of databases including PubMed, Embase, and Cochrane Library was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 43 publications
3
73
0
1
Order By: Relevance
“…Strong repair capabilities of young patients may lead to this, but they also have a higher impact on loading activities. Octavian A found in a meta-analysis that 38% of the 1,134 hips that underwent core decompression had THA at an average follow-up time of 26 months [18]. Core decompression combined with other therapies(bone marrow stromal cells) can also achieve good results in the early stages of femoral head necrosis [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Strong repair capabilities of young patients may lead to this, but they also have a higher impact on loading activities. Octavian A found in a meta-analysis that 38% of the 1,134 hips that underwent core decompression had THA at an average follow-up time of 26 months [18]. Core decompression combined with other therapies(bone marrow stromal cells) can also achieve good results in the early stages of femoral head necrosis [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of alendronate for treating ONFH has been questioned by later studies [35,36]. Core decompression is believed to be the most reliable operative treatment for precollapse ONFH [37]. Even so, an RCT study published in 2017 reported a mean HHS of 68 AE 5 in 21 patients who had undergone core decompression surgery at 3 years follow-up visit [33].…”
Section: Discussionmentioning
confidence: 99%
“… 13 A meta-analysis showed that core decompression in combination with tantalum rod implantation gave satisfactory clinical results. 14 Auregan et al found that the mechanical support for femoral head may be improved through core decompression and insertion of a tantalum rod. 15 Moreover, Moya-Angeler et al reported that porous tantalum implants combined with core decompression provided structural support, without causing autograft harvest or infectious complications of bone allograft.…”
Section: Discussionmentioning
confidence: 99%